RSSI based tracker system / Ahmad Kamarul Arifin Zulkifli, Mohd Haziq Iqman Hamsah and Amirah Salimun - Zulkifli, Ahmad Kamarul Arifin; Hamsah, Mohd Haziq Iqman; Salimun, Amirah (2015)
Tracking a lost object is very common problems that are experienced by everyone. It will very hard when the object we are searching is small in size. The aim of this project is to implement a tracking system that is able to locate an item anywhere. The RSSI (Received Signal Strength Indicator) based tracker that we build uses two receiver attached with antenna that will receive the signal from the transmitter and compare the signal strength either it stronger at the right antenna or at the left antenna. The signal strength value is obtained at two of the receiver pin, which is RSSI pin. The comparison of the RSSI value made by the Arduino and it will be used to determine the location of the transmitter by providing the output in form of the LCD.